The Attempted Suicide in Chiang Mai : A Case Study of Nakhornping Hospital - Metatratip, Prasit; Vongverapant, Matree (Journal of Health Science of Thailand, 2018)
The purpose of this prospective study was to investigate the characteristics of people who attempted suicide in Chiang Mai. The target population was people who attempted suicide and received treatment at Nakornping hospital during the 3 year period October 2004- September 2007. In the group of those who attempted suicide, the majority of victims were in the age group of 15-24 year (42.0%), most consumed poisonous substances (89.9%). As for warning signs, 34.5 percent in attempted suicide group had related suicidal inclinations at least once to their close relatives or friends. As such, the forewarning signs could be recognized and become one of crucial cores of a preventive program. The causes of suicide were multi-factorial component. In attempted suicide, problems about family members and lovers were the most common (66.4%) and economic problems prevailed (26.0%). As for depression, 44.5 percent in attempted suicide group met the criteria for depressive episode (F32). The results of this study could be applied to suicide prevention programs to decrease suicide rates in other provinces of Thailand.